Study of charge density distributions, elastic and inelastic electron scattering form factors and size radii for 19F and 27Al Nuclei - Zaid M. Abbas and Ghaith N. Flaiyh (Cuestiones de Fisioterapia, 2024)
Unitary Correlation Operator Method (UCOM) have been used to examine the ground state properties of 19F and 27Al nuclei such as, the charge densities, the root mean square (????????????) radii, elastic electron scattering form factors. Inelastic longitudinal electron scattering form factors have been computed for isoscaler transition